Mapping the path to decarbonised agri‐food products: a hybrid geographic information system and life cycle inventory methodology for assessing sustainable agriculture - Martindale, Wayne; Saeidan, Ali; Tahernezhad‐Javazm, Farajollah; Hollands, Tom Æ; Duong, Linh; Jagtap, Sandeep (Wiley, 2024)
The development of a decarbonised food industry will depend on a sustainable agricultural system where embodied food product greenhouse gas emissions (GHG) can be associated with agricultural production. The method presented demonstrates how mapping agri‐production can be used to calculate regional carbon footprints so GHG emission reduction is geographically strategic. Different agronomic and husbandry outcomes are mapped using Geographic Information Systems (GIS's) and carbon footprints are calculated using Life Cycle Inventory (LCI) libraries. The hybridised GIS‐LCI approach reports unique insights for decarbonisation, demonstrating how farming practices can be further integrated to best deliver food security. We use the GIS‐LCI method to show; (1), geography limits crop and livestock production types; (2), agri‐product density data can be used to calculate a food system carbon footprint; and (3), GIS's can be used to focus food policy for sustainability.
Keywords: Decarbonisation; food manufacturing; food security; food supply; sustainability; 30 Agricultural, Veterinary and Food Sciences; 3006 Food Sciences; 2 Zero Hunger; 12 Responsible Consumption and Production; Food Science; 3006 Food sciences; 3210 Nutrition and dietetics; 4004 Chemical engineering